The Sound and Fury of Carried Interest Reform - Burke, Karen C. (Columbia Journal of Tax Law, 2010)
Of all the proposals advanced in recent years to reform Subchapter K, the part of the Internal Revenue Code (“IRC” or “Code”) governing partnership tax, perhaps none has generated more acrimony and confusion than the pending carried interest legislation contained in proposed § 710.1 While reformers have framed the issue of taxing the compensatory portion of a service partner’s return as ordinary income in terms of distributive justice, critics have been quick to invoke the rhetoric of class warfare to fend off reform. In the most elementary terms, the carried interest legislation would tax some (but not all) of a service partner’s share of partnership profits as ordinary income. Even at this basic level, however, the contours of the proposed legislation are ambiguous. Indeed, the reform is sometimes misdescribed as taxing “distributions” rather than “distributive shares” as ordinary income, a distinction that is fundamental. Moreover, the precise tax advantage of carried interest arrangements depends crucially on whether one adopts a “joint-tax” perspective or focuses more narrowly on the service partner’s opportunity for deferral and conversion. Apart from the merits of carried interest legislation, there is also considerable dispute over whether such reform is likely to raise significant amounts of revenue.